Analisis Pemanfaatan Repositori Institusi Oleh Mahasiswa Universitas Putra Indonesia Yptk Padang - Syafitri, Annisa Rini; Erlianti, Gustina (Departemen Informasi Perpustakaan dan Kearasipan, 2024)
This study analyzes the use of institutional repositories by Universitas Putra Indonesia YPTK Padang students as a source of academic reference. Using a quantitative descriptive approach, data was collected through a questionnaire distributed to 100 students. The results showed that this repository supports cost savings, provides easy and quick access to academic resources, and is relevant to lecture needs. However, students' awareness of the term